The phantom thief - Rashford, Marcus; Kissi, Marta; Koya, Alex Falase (London Macmillan, 2023)
A mysterious figure is stealing from clubs all over Rutherford High! The only clue is a strange calling card left at the scene of the crime. When the thief strikes just as Art Club is getting ready for a big show, everyone is worried the exhibition will be cancelled. As suspicion falls on one of the Breakfast Club Investigators, Marcus and friends must race against time to find the stolen painting and unmask the true thief before it's too late!"--Publisher's description
English stories
Keywords: Children's stories; English stories